Food and nutrition surveillance system in municipalities of paraíba: data reliability, coverage and management's perception - Dixis Figueroa Pedraza (Universidad de Antioquia, 2017)
Objectives: To evaluate the reliability of anthropometric data of under-five children based on the SISVAN-Web, describing the coverage of the System and aspects of its implementation. Methods: Cross-sectional study developed in two cities of Paraíba. The sample consisted of 18 family health teams and 324 children, randomly selected. Anthropometric measures (weight and height) were collected (1) by the researcher using standard equipment (R); (2) by the researcher using service equipment (RS) and; (3) during routine service (S). Municipal managers answered a questionnaire about the System. Results: Among the 319 children observed, 10.28% were overweight/age, 14.02% were overweight and 7.16% were stunted. Coverage was 2.8% in one municipality and 3.3% in the other, being higher for children and smaller for the elderly. The agreement between S and R were weaker than those with RS, especially for height/age (Kappa=0.38) and BMI/age (Kappa=0.39). The measurements obtained in S overestimated overweight and stunting. Managers mentioned that the information of the System is restricted to the health sector. Conclusions: The study pointed to major shortcomings related to SISVAN-Web. The system's coverage and reliability of anthropometric measurements were both low. The System is not used to its full potential.